The Effect of Job Insecurity and Job Stress on Turnover Intention Among Retail Store Employees at Pusat Grosir Cirebon - Tiara Adelin Surya; Editya Nurdiana (Greenation Research & Yayasan Global Resarch National, 2026)
This study aims to analyze the effect of job insecurity and job stress on turnover intention among retail store employees at Pusat Grosir Cirebon. The research employed a quantitative approach using a survey method involving 100 respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that job insecurity and job stress have a positive and significant effect on turnover intention, both partially and simultaneously. The coefficient of determination shows that these two variables explain a substantial proportion of the variation in employees’ turnover intention. These findings highlight the importance of managing job security and work-related stress as part of efforts to enhance employee retention in the retail sector.